Vitrification affects the post-implantation development of mouse embryos by inducing DNA damage and epigenetic modifications - Yurong Chen; Haibo Zhu; Fucheng Guo; Luyao Wang; Wenli Zhang; Ruizhi Liu; Xiaoling Zhang; Xiangpeng Dai (Clinical Epigenetics)
Abstract Vitrification is widely used in assisted reproductive technology (ART) for female infertility, but the long-term effect on the embryo of vitrification has not been comprehensively studied. The study aimed to investigate the effect of vitrification on long-term development of mouse embryos. The warmed embryos which were frozen at 8-cell stage were cultured in vitro until the blastocyst stage and were transferred into recipients. Immunofluorescence staining was performed to evaluate the reactive oxygen species (ROS) level, mitochondrial function, cell apoptosis, DNA damage and histone epigenetic modification in blastocysts. Transmission electron microscopy (TEM) analysis was performed to exam the mitochondrial ultrastructure in blastocysts. The related gene expression and transcriptome profiles were investigated by RT-qPCR and RNA-seq, respectively. Blastocyst and implantation frequencies were not significantly affected by vitrification. However, vitrification significantly reduced blastocyst cell number and the live pup frequency. Vitrification induced ROS accumulation, DNA damage, and apoptosis in mouse blastocysts. The homologous recombination (NHEJ) is the major DNA repair pathway for vitrified embryos. Vitrification elevated H3K4me2/3, H4K12ac, and H4K16ac levels and reduced m6A modification in blastocysts. Moreover, vitrification significantly altered transcriptome profiles of mice placentas and brains at embryonic day 18.5 (E18.5). Thus, vitrification exhibited a long-term effect on mouse embryo viability by increasing ROS levels, DNA damage, altering the epigenetic modifications and transcriptome profiles.